Dental Stain pada Atlet Renang - Melati, Bingah (Bhakta Dental Journal, 2024)
Dental stains (extrinsic staining of the teeth) can occur in swimmers with intensive training intensity for more than 6 hours a day and exposure to pool water for a long time. One of the contents of pool water is Chlorine which contains hypochloric acid with an acidic pH of around 2.7 - 4. Case report on a 16-year-old male with complaints of yellowing front teeth that appeared after approximately 1 year of regular swimming practice at one of the Solo City swimming pools. The results of the intraoral examination obtained good oral hygiene, no caries, stains on 13, 12, 11, 21, 22, 23, 24, 35, 34, 33, 32, 31, 41, 42, 43, 44, 45. The treatment given was scalling, giving oral hygene instruction, IEC related to maintaining oral hygiene by brushing teeth and tongue with a soft toothbrush at least twice a day. There was significant improvement and change after treatment of the child's teeth.